Implementasi Human-centered Design pada Perancangan Interior Stress-Relieve and Entertainment Centre di Surabaya - Evania Tjandra; Diana Thamrin; Linggajaya Suryanata (Intra, 2019)
According to a research that has been studied by WHO (World Health Organization), as many as 800.000 people commit suicide every year, which means that in every 40 seconds, one person dies by commiting suicide. Mental illness such as depression, anxiety disorders, and other illnesses are often caused by stress. Even though being stressed is considered normal, if the conditions become worse, it would give negative impacts to the body, and one of them is suicide. Brain Rest Area exists with a purpose to create ambiences and interior systems that would help stressed people feel better, and also provide education about the importance of mental health, so the public would be able to empathize with the stressed people. Brain Rest Area design applies the biophilic and healing environment design methods, supported by human-centered design and empathic design approaches. The result of this design concludes that Brain Rest Area can be an alternative facility for the stressed people, supported by the programs that help stress’ healing process, such as non-medical (cognitive) therapies in feeling rooms, pillow pools, clinics, volunteer booths, meditation, and other facilities, with the concept of Brain Rest Area itself that focusses on giving a rest to the brain, by relieving fatigue and giving relaxing moments for the stressed people.